2006
DOI: 10.1016/j.jphotobiol.2006.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of tetraaryl-porphyrin photosensitizers: An in vitro study on Gram negative and Gram positive bacteria

Abstract: The reported results confirm that the presence of positively charged groups on porphyrin frame is fundamental for PSs antibacterial activity, however our data suggest that a moderate degree of lipophilicity, achievable by the introduction of aromatic hydrocarbon side chains on the pyridyl moieties, may improve PSs efficiency. Furthermore dicationic porphyrin 7 seems to be more efficient than the corresponding tetracationic derivatives thus emphasizing an interesting feature involved in the PSs activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
136
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(148 citation statements)
references
References 28 publications
8
136
2
2
Order By: Relevance
“…It has been showed that values close to zero induce their aggregation, thereby reducing the antimicrobial activity [53], on the contrary if these values are too high (>40 Mv), dark toxicity is present [54], whereas negative potentials result in repulsion between bacterial cells and nanoparticles. An important parameter is the surface charge of liposomes [55]. In particular, cationic liposomes are more effective than neutral or anionic ones in aPDT because of the establishment of electrostatic attraction with the negatively charged cell wall, which facilitate the interaction of liposome to microbial wall, and then the delivery of the PS into the microbial cells.…”
Section: Photomedicine -Advances In Clinical Practicementioning
confidence: 99%
“…It has been showed that values close to zero induce their aggregation, thereby reducing the antimicrobial activity [53], on the contrary if these values are too high (>40 Mv), dark toxicity is present [54], whereas negative potentials result in repulsion between bacterial cells and nanoparticles. An important parameter is the surface charge of liposomes [55]. In particular, cationic liposomes are more effective than neutral or anionic ones in aPDT because of the establishment of electrostatic attraction with the negatively charged cell wall, which facilitate the interaction of liposome to microbial wall, and then the delivery of the PS into the microbial cells.…”
Section: Photomedicine -Advances In Clinical Practicementioning
confidence: 99%
“…41 Inefficient killing of Gram-negative species relative to Gram-positive by photoactivation has been known for almost 30 years 43 as well as the value of adding a membrane-disrupting agent to enhance access of the photo-sensitizer. However, other effective approaches include using agents with strong cationic charge to enhance binding to Gram-negative bacteria 44 and liposome encapsulation to enhance delivery by fusion with the membrane. 45,46 In each case though, the degree of killing will still depend upon the efficiency of the photosensitizer being used.…”
Section: Light-activated Killingmentioning
confidence: 99%
“…cytotoxicité est exprimée comme la concentration de l'extrait ou composés inhibant la croissance des cellules de 50% (IC50). Les manipulations sont similaires à celle rapportée dans la littérature par notre groupe [Sylvestre M., 2006] 2.3.2 Évaluation de l'activité antibiotique L'activité antibactérienne a été évaluée en utilisant la méthode décrite par [Banfi, 2006] avec quelques modifications. Brièvement, les bactéries à croissance exponentielle ont été inoculés dans des plaques 96 puits à fond rond.…”
Section: Utilisation En Médecine Traditionnelle Du Pin Gris (Pinus Bunclassified